Physiological diversity in tolerance to water deprivation among species of South American desert rodents - Bozinovic, F.; Cruz-Neto, A. P.; Cortes, A.; Diaz, G. B.; Ojeda, R. A.; Giannoni, S. M. (Elsevier B.V., 2007)
Rodents from and and semi-arid deserts are faced with the problem of water conservation. The physiological responses of small rodents to such conditions have been intensively investigated over broad geographically disjunct areas. Despite the presence of xeric habitats in South America since the late Tertiary, some studies suggest that sigmodontine South-American desert rodents do not display the same diversity of physiological responses at the species level as those observed in other desert-dwelling species of rodents. In this paper, we analyzed the physiological responses to water deprivation, at the interespecific and interindividual level, among eight species of sigmodontine desert-dwelling rodents from different geographical areas within South-American deserts. Using randomization tests, we found no significant phylogenetic signal for resistance to water deprivation or for individual variability in this response. Contrary to our initial predictions, we observed that sigmodontine rodents from arid/semi-arid habitats (Monte Desert) had significantly lower rates of body mass loss per day (higher tolerances to water deprivation) than species from the hyperarid deserts. We showed that sigmodontine rodents from South America showed a remarkable diversity of physiological mechanisms for coping with water shortage resulting from different evolutionary adaptive strategies. This diversity, however, displays a rather unexpected pattern in terms of its geographical distribution. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: body mass balance; geographic comparisons; physiological tolerances; water economy